Hands-on reactive programming with Java 12 - Lelek, Tomasz (Packt Publishing, 2019)
"Reactive programming is a programming paradigm oriented toward data flows and the propagation of change: programming with asynchronous data streams. Apps in recent times have an abundance of real-time events of every kind that create a highly interactive experience for the user. However, the right tools are needed to manage these, and Reactive programming is the answer. This course is a step-by-step guide to creating applications with Java 12 by applying Reactive programming. You will get hands-on experience; each section will build on the previous one, so that you will be able to make your app responsive and reliable by implementing Reactive principles with Java. You'll also apply the best data structures and algorithms that optimize functions--all using functional Reactive programming."--Resource description page